DIFFERENCES IN THE INCIDENCE OF ANEMIA IN PREGNANT WOMEN BASED ON MATERNAL OBSTETRIC STATUS - Fridalni, Nova; Yanti, Etri; Wahyuningsih, Sri (STIKES Syedza Saintika Padang, 2023)
Anemia in pregnancy is a common problem because it reflects the socio-economic welfare of society and has a very large influence on the quality of human resources. Anemia in pregnant women is called potential danger of mother and child, which is why anemia requires serious attention from all parties involved in health services in the future. Anemia in pregnancy has an adverse effect on the mother, both during pregnancy, childbirth and in the postpartum period. Various diseases can arise due to anemia such as abortion, premature labor, prolonged labor due to uterine inertion, shock, infections both intrapartum and postpartum. The aim of this study was to determine the proportion of anemia in pregnant women based on their obstetric status. This type of research is descriptive with a cross sectional approach. The research was conducted at Puskesmas Andalas Padang in May 2023, with a sample size of 58 pregnant women who met the criteria set by researchers. Data analysis was carried out univariately by displaying a frequency distribution table. The results of the study showed that a higher proportion, namely 74.1% of pregnant women experienced anemia, where the incidence of anemia was found to be higher in pregnant women who were grande multigravida, multipara and with pregnancies less than 2 years apart. It can be concluded that the obstetric status of pregnant women is related to the incidence of anemia in pregnancy. Keywords: Pregnant women, anemia, obstetric status.